Effects of heat treatment process and hot isostatic pressing on microstructural evolution of high-niobium TiAl alloy - Ziqi Gong; Ziyong Chen (AIP Advances)
In this paper, the vacuum induction levitation melting method was adopted to prepare high-niobium TiAl-based alloys. The microstructure of the alloys was analyzed by means of optical microscopy, scanning electron microscopy, and other means, and the influence of heat treatment/hot isostatic pressing on the microstructure evolution of the alloys was studied. The research findings are as follows: During annealing at 1250 °C, with the increase in holding time, the content of the β phase in the alloy gradually decreased, while the number of α2 laths increased and the α2 lamellae became finer. After heat treatment at 1280 °C for 4 h, only a small amount of the β phase remained in the microstructure. When the holding time was increased to 8 h, the β phase in the alloy matrix was basically eliminated, and the size of the lamellar colonies in the microstructure increased. Hot isostatic pressing treatment at 1250 °C/200 MPa for 4 h could eliminate the β phase in the alloy, and both the grain size and the lamellar spacing of the alloy were significantly reduced compared with those after heat treatment at 1250 °C for 4 h. Hot isostatic pressing treatment at 1280 °C/200 MPa for 4 h could eliminate the β phase in the alloy while causing the α2 lamellae in the microstructure to coarsen.